Nitrogen critical interval and sampling season in Coffea canephora in Cambisol soils - Pérez-Díaz, Alberto (2023)
Introduction. The commercial introduction of Coffea canephora in Cuba occurred in 1930. Research on nitrogen fertilizer requirements has been conducted, but has not included foliar analysis as a criterion for the diagnosis of nutritional status. Objective. To establish the critical intervals of foliar nitrogen content and the most appropriate sampling moment to propose corrections to nitrogen fertilization in coffee. Materials and methods. The investigation was carried out between 2008 and 2011. The response of the coffee plants to nitrogen doses (0, 50, 100, 150, 200 kg ha-1) was studied in a randomized block experimental design with four replicates in soils of the Cambisoles order. Leaf sampling was carried out at the stages of flowering, fruiting, grain growth, and beginning of maturation. The relationships between relative yield and fertilizer doses were determined, as well as between the foliar N concentrations and relative yield. The critical range of N contents (%) that allowed reaching 90 % to 100 % of the relative yields was estimated. Results. Critical nitrogen intervals (ICN) for yields between 90 % and 100 % were similar among years and locations for fruiting, although they varied among phenological stages. The highest foliar concentrations and the widest range of these (2,79–2,97 % N) were found at the beginning of fructification, which was considered the most appropriate time to correct the fertilization system employed. There was a relationship between the relative annual crop yields and the N foliar concentrations for the robusta coffee plants. Conclusions. The critical nitrogen intervals of foliar N in coffee plants was established in the fruiting stage with a concentration of 2.79 %. Sampling at the beginning of fruiting was the most appropriate to assess the correction of nitrogen fertilization.